Practical controller for precision positioning system - A new design approach and application to mechanism with friction - Chong, Shin Horng; Sato, Kaiji (2010)
This paper describes an improvement of a practical controller design for high precision motion performance. For practical use, high motion control performance and ease of controller design are desired. A nominal characteristic trajectory following control (NCTF control) has been studied to satisfy the desired performance. The NCTF controller consists of a nominal characteristic trajectory (NCT) which is the reference motion of control system and a PI compensator which makes the motion of the controlled object to follow the NCT. The NCT is easily determined from the experimental open-loop time responses of the mechanism. The controller parameters can be also determined easily, without any given model parameters. Up to now, the NCTF controllers have been improved steadily to enhance its performance in positioning and continuous motion control. The Continuous Motion NCTF controller has been proposed to improve control performance of continuous motion such as tracking and contouring motions. The experimental results indicate that the Continuous Motion NCTF controller is more suitable in all the motion control as compared to the conventional NCTF controller. However, the current NCTF controllers have addressed the less accuracy of following characteristic on nominal characteristic trajectory to meet high precision motion specification. The object motion does not follow the NCT perfectly near the origin on phase plane. This phenomenon often indicates unwanted overshoot and low motion accuracy. In the present paper, a practical solution is provided to improve the Continuous Motion NCTF controller for reduction of the motion error and increase of robustness of the control system. The improved practical controller is referred to as the Acceleration Reference – Continuous Motion NCTF controller (AR-CM NCTF controller). The AR-CM NCTF controller serves in improving the following characteristic of the object motion on NCT near origin and providing the high overshoot reduction characteristics and high robustness control system. The AR-CM NCTF controller includes the Continuous Motion NCTF controller structure. Besides the velocity reference, the acceleration reference for object motion is used as the additional controller elements. The constructed NCT and designed PI compensator of the Continuous Motion NCTF controller are adopted in implementing the AR-CM NCTF controller. The design procedure of the AR-CM NCTF controller remains easy, practical and is independent of friction characteristics. The AR-CM NCTF controller has been implemented to a non-contact mechanism and promising results are proved. In this paper, the effectiveness of the AR-CM NCTF controller was examined in positioning and tracking motion performances using contact mechanism. A disturbance observer with PD compensation (PDDO) control system was designed and compared with the AR-CM NCTF controller. The experimental results demonstrate that the AR-CM NCTF controller yields excellent positioning and tracking performance and higher robustness to plant parameter variations, as compared to the Continuous Motion NCTF and PDDO controllers.